Light Lanthanide Metallocenium Cations Exhibiting Weak Equatorial Anion Interactions. Issue 32 (13th May 2019) - Liu, Jingjing; Reta, Daniel; Cleghorn, Jake A.; Yeoh, Yu Xuan; Ortu, Fabrizio; Goodwin, Conrad A. P.; Chilton, Nicholas F.; Mills, David P.
Abstract: As the dysprosocenium complex [Dy(Cp ttt )2 ][B(C6 F5 )4 ] (Cp ttt =C5 H2 t Bu3 ‐1, 2, 4, 1‐Dy ) exhibits magnetic hysteresis at 60 K, similar lanthanide (Ln) complexes have been targeted to provide insights into this remarkable property. We recently reported homologous [Ln(Cp ttt )2 ][B(C6 F5 )4 ] (1‐Ln ) for all the heavier Ln from Gd–Lu; herein, we extend this motif to the early Ln. We find, for the largest Ln III cations, that contact ion pairs [Ln(Cp ttt )2 (C6 F5 ‐κ 1 ‐ F )B(C6 F5 )3 ] (1‐Ln ; La–Nd) are isolated from reactions of parent [Ln(Cp ttt )2 (Cl)] (2‐Ln ) with [H(SiEt3 )2 ][B(C6 F5 )4 ], where the anion binds weakly to the equatorial sites of [Ln(Cp ttt )2 ] + through a single fluorine atom in the solid state. For smaller Sm III, [Sm(Cp ttt )2 ][B(C6 F5 )4 ] (1‐Sm ) is isolated, which like heavier 1‐Ln does not exhibit equatorial anion interactions, but the Eu III analogue 1‐Eu could not be synthesised due to the facile reduction of Eu III precursors to Eu II products. Thus with the exception of Eu and radioactive Pm this work constitutes a structurally similar family of Ln metallocenium complexes, over 50 years after the [M(Cp)2 ] + series was isolated for the 3d metals. Abstract : Metal sandwiches : A family of light lanthanide metallocenium cations is reported. For the largest members of this series, equatorial interactions with a weakly coordinating anion are observed.